Negotiating the expertise paradox in new mothers' WhatsApp group interactions. (October 2020) - Lyons, Agnieszka
Abstract: This paper reports on a discourse-ethnographic study of WhatsApp communication between new mums affiliated with the National Childbirth Trust (NCT). The data consists of over 600 screenshots collected over a 13-month period and supplemented by semi-formal interviews. The focus is on the nature of NCT WhatsApp messaging, with its semi-private character, as a platform for gathering and evaluating knowledge, sharing embodied experiences, and self-positioning with respect to medical professionals and medical advice. Analysis focuses on the process of constructing and de-constructing expertise and negotiating the expertise paradox, which involves new parents being positioned as fully responsible for their child's wellbeing and development, while also requiring training in the art of childcare provided by health care professionals. With virtually unrestricted access to information, mothers are expected to act as responsible moral actors, evaluating existing advice, managing cultural expectations and adopting a highly reflexive orientation to their maternal responsibilities. The study shows that, through an ongoing WhatsApp engagement with each other, new mums create a pool of parenthood-related expert and experiential knowledge, which is both similar and different from that experienced in "intimate mothering publics" (Johnson 2015) online.